ISOLATION AND IDENTIFICATION OF NON-POLAR CHEMICAL ENTITY FROM LEPTADENIA RETICULATA AERIAL PARTS - DHALANI, JAYESH; NARIYA, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Leptadenia reticulata is the medicinal plant having many biological activities. It is necessary to find out which types of phytochemical constituents are present in the plant. The objective of this investigation was to isolate and identify the non-polar chemical entity of the areal parts of L. reticulata a plant used for medicinal purpose in folklore. Methods: Petroleum ether extract of the stem bark was used for this study. Non-polar solvent was used to extract non-polar chemical entity from areal parts of leptadeniareticulata. Through the saponification process, saponifiable and unsaponifiable matter was separated. Phytochemical constituents were separated using column chromatography. Separated fractions were analyzed on gas chromatography and mass spectrometry (GC-MS) and nuclear magnetic resonance spectroscopy (NMR). Results: Hentriacontane compound was isolated and confirmed from GC-MS and NMR whereas phytol, Lupeol, β-amyrin, Campesterol, Stigmasterol, gamma-sitosterol identified through GC and mass spectroscopy. Conclusion: The present study showed that L. reticulata areal parts three sterols chemical entity Campesterol, Stigmasterol, gamma-sitosterol and phytol (diterpene alcohol), lupeol (triterpenoid), beta-amyrin (triterpene), and hentriacontane (alkane hydrocarbon). Core determination of the experiment was the development efficient method to isolate or identify the non-polar chemical entity through chromatographic technique.